ANALYSIS OF PRODUCT LINE PROFITABILITY USING THE FULL COSTING METHOD AT MSME MING ART FLORIST IN KARAWANG - Sodik, Fajar Japar; Sekarsari, Dewi; Adidjaya, Fawwaz Rippa Gilardi; Maharani, Chika; Sukriyansyah, Deden; Situngkir, Tiar Lina (Journal for Management Student (JFMS), 2024)
This study aims to analyze the profitability of various product lines at MSME Ming Art Florist using the full costing method. MSMEs play an important role in the economy, and the accuracy of production cost calculations is a key factor in determining competitive selling prices. The full costing method includes all costs, both fixed and variable, in calculating the cost of goods manufactured, resulting in a more detailed understanding of the costs and profit margins of each product. The research was conducted by collecting historical sales data, raw material, labor, and overhead costs. Analysis was conducted to identify the most profitable product lines and provide strategic recommendations to improve cost efficiency and competitiveness. The results show that the artificial flower bouquet product line contributes greatly to profitability, while other products (snack bouquet) require innovation or cost reduction. In conclusion, the application of the full costing method can help Ming Art Florist improve operational efficiency and make more strategic decisions in product development and pricing.